Snail Augments Nuclear Deformability to Promote Lymph Node Metastasis of Head and Neck Squamous Cell Carcinoma - Chen, Yin-Quan; Hung, Chen-Yu; Wei, Ming-Tzo; Kuo, Jean-Cheng; Yang, Muh-Hwa; Cheng, Han-Ying; Chiou, Arthur (Frontiers in Cell and Developmental Biology, 2022)
Up to 50% of head and neck squamous cell carcinoma (HNSCC) patients have lymph node (LN) metastasis, resulting in poor survival rate. Numerous studies have supported the notion that the alterations of gene expression and mechanical properties of cancer cells play an important role in cancer metastasis. However, which genes and how they regulate the biomechanical properties of HNSCC cells to promote LN metastasis, remains elusive. In this study, we used LN metastatic mouse model in vivo to generate an LN metastatic head and neck squamous cell carcinoma cell line and compared the differences in the bio-molecular and biomechanical properties of LN-metastatic and non-metastatic cells. Our results showed that LN-metastatic cells had a higher level of Snail expression compared to non-LN metastatic cells. The higher Snail expression promoted cellular invasion capability in confined environments mainly by increasing the longitudinal strain of the cell nuclei, which could be attributed to stronger cell traction force and softer nuclear stiffness. These two biomechanical changes were correlated, respectively, to larger amount of focal adhesion and less amount of nuclear lamins. Taken together, our works revealed not only the biomechanical profiles of LN metastatic cells, but also the corresponding biomolecular expressions to pinpoint the key process in LN metastasis.